A Case of Juvenile Onset Neuronal Intranuclear Inclusion Disease With a Negative Antemortem Skin Biopsy. (September 2018) - Pilson, Keith; Farrell, Michael; Lynch, Bryan; Devaney, Deirdre
Neuronal intranuclear (hyaline) inclusion disease (NIID) is a rare neurodegenerative disorder with a variable clinical presentation and multiple subtypes. We present the clinicopathologic details of a patient with juvenile-onset NIID and discuss the pathogenesis. We also discuss the utility of antemortem skin biopsy which was negative in our case.